169 A quasi experimental uncontrolled before-after study to assess impact of cashe interventions in the year 2016–2017 at petrochemical industry. (24th April 2018) - Shah, P; Rajesh, R; Dave, P
Abstract : Introduction: To inculcate best practices in the field of OH; RIL has launched the initiative in 2003 known as CASHe in all 7 manufacturing sites. The various interventions under this project are excellent examples of team work of medical, safety, environment and technical department of respective manufacturing sites. Previously there wasn't any scientific research approach to evaluate their outcomes at RIL-DMD-which is amongst the largest petrochemical site of RIL. So the present study was carried out to address this need. Methods: There are total 12 manufacturing plants and each of them were considered as a unit of the study. The secondary data from all these 12 plants were collected going 1 year retrospectively using semi-structured proforma regarding various CASHe interventions and compiled using MS Excel 2007. Data triangulation was done using OHC data (IH Surveys and HMIS) with plant data. After necessary editing and exclusion (i.e. projects lacking before-after data, qualitative data) student paired T test was applied to find out statistical significance. Result: There were total 187 interventions (mean-15.58/plant) addressing noise, heat, chemical exposure, ergonomics, safety and environmental hazards. Out them 142 completed and 45 in progress. Total 3316 persons (928 employee and 2388 contract workers) trained for different OH training with average 600 man hours/department. Central theme for CASHe: 2016–2017 achieved statistically significant result in term of reduction in no. of Pre-diabetic cases up to 30% compared to previous year. Other significant interventions were reduction in exposure to benzene vapour by vapour recovery unit (p=0.01), noise (p=0.001) and heat etc. Discussion: CASHe projects outcomes were successful in terms of reducing hazards, workplace improvements and wellness of employee. So the present study experiments guide other industries to deal with noise, heat, highly toxic material safely and reduce their exposure along with taking care of life style diseases of their employees.